Intelligent scheduling method for energy saving operation of multi-train based on genetic algorithm and regenerative kinetic energy - Zou, Bingqian; Gong, Lixiong; Yu, Ning; Chen, Jin (Journal of engineering (Stevenage, England), 2018)
An intelligent scheduling method for energy saving operation of multi-train is proposed based on genetic algorithm and regenerative kinetic energy. Considering the morning and evening peak, departure time, and total vehicle number, the energy consumption optimisation model of multidimensional state vector subspace of train is established for the train departure interval with the lowest total energy consumption. Two intelligent control models are used to formulate the time interval scheduling plan depending on whether to consider the morning and evening peak. The train operation diagram is solved by Matlab, and the validity and feasibility of the proposed algorithm are verified. This study provides an intelligent and efficient algorithm and solution for multi-train intelligent scheduling problem.